Financing services sector: Effectiveness of operational coordination and process control, evidence from Malaysia - Mohd Yaziz bin Mohd Isa; Gazi Md. Nurul Islam; Zulkifflee Mohamed (Global Business & Finance Review (GBFR), 2020)
Purpose: The paper assesses effectiveness of a financing scheme for services sector entrepreneurs by a financial development institution in Malaysia based on the competencies measurement for entrepreneur in services sector, i.e. productivity and service delivery effectiveness Design/methodology/approach: The study employed 20 questionnaires based on the competencies measurement for entrepreneur in services sector Findings: The results provided a better understanding of the entrepreneurial competencies, performance before and after receiving the financing, and the competitive environment facing the entrepreneurs in the services sector to mitigate negative impacts to their business and general economy following the extended recovery movement control order (CMCO) because of covid-19 pandemic in Malaysia until 31 December 2020. Research limitations/implications: The sample size that limits to companies currently servicing loans is a limitation Originality/value: The paper studied an actual financing scheme for services sector entrepreneurs by a financial development institution
Keywords: 650; Financing services sector; productivity and service delivery effectiveness; operational coordination; process control